Analisis Hubungan Persiapan Persalinan Ibu Hamil Trimester III Dengan Tingkat Kecemasan Saat Pandemi Covid-19 Di BPM R Jatijajar Kota Depok - Shindy Marshela; Andi Mayasari Usman; Retno Widowati (MAHESA : Malahayati Health Student Journal, 2022)
ABSTRACK                                       Coronaviruses are a large family of viruses that cause disease in humans and animals. In humans it can cause respiratory tract infections, ranging from the common cold to serious illnesses such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). The COVID-19 pandemic has been recognized as a trigger for anxiety, especially in pregnant women. Pregnant women are a vulnerable population at risk  of contracting the COVID-19 virus. The Covid-19 phenomenon has become a multidimensional disaster that has occurred in various countries, including Indonesia. So adaptation is needed  in responding to changes that can overcome physical and mental problems in society, especially the adaptation of pregnant women in preparation for childbirth during the COVID- 19 pandemic. To find out the relationship between preparation for delivery in third trimester pregnant women and the level of anxiety during the COVID-19 pandemic. This study uses a quantitative method with a cross sectional approach. Sampling using total sampling technique with a sample of 34 people. The measurement method is using a questionnaire with a measuring instrument using a questionnaire and the data obtained will be analyzed univariately and bivariately using the Chi Square test. The results showed that there were 25 pregnant women aged 21-35 years (73.5%), with a job as a housewife as many as 25 people (73.5%), and pregnancy with their first child as many as 18 people (47.4 %), with good delivery preparation as many as 29 people (85.3%) and a very severe level of anxiety as many as 21 people (61.8%). Based on the results of the Chi Square calculation, P-value 0.000 <0.05 is obtained, which means that H0 is rejected and Hα is accepted. There is a relationship between the preparation for delivery of pregnant women in the third trimester and the level of anxiety during the covid-19 pandemic. It is hoped that health workers can maintain regular counseling to pregnant women about preparation for childbirth and about anxiety in pregnant women during examinations.Keywords : Covid-19, Anxiety, Childbirth Preparation ABSTRAK Coronavirus adalah keluarga besar virus yang menyebabkan penyakit pada manusia dan hewan. Pada manusia bisa menyebabkan penyakit infeksi saluran pernapasan, mulai flu biasa hingga penyakit yang serius seperti Middle East Respiratory Syndrome (MERS) dan Sindrom Pernafasan Akut Berat/ Severe Acute Respiratory Syndrome (SARS). Pandemi covid-19 telah diakui sebagai pemicu kecemasan, terutama pada wanita hamil. Wanita hamil termasuk populasi rentan yang beresiko tertular virus covid-19. Fenomena covid-19 ini menjadi sebuah bencana multidemensional yang terjadi di berbagai negara termasuk Indonesia. Maka dibutuhkan adaptasi dalam merespon perubahan yang dapat mengatasi permasalahan fisik dan mental di masyarakat terutama adaptasi ibu hamil dalam persiapan persalinan di masa pandemi covid-19. Tujuan penelitian ini untuk memperjelas adanya hubungan antara persiapan persalinan pada ibu hamil trimester III dengan tingkat kecemasan selama masa pandemi covid-19. Penelitian ini menggunakan metode kuantitatif dengan pendekatan cross sectional. Pengambilan sampel menggunakan teknik total sampling dengan sampel sebanyak 34 orang. Cara ukur menggunakan angket dengan alat ukur menggunakan kuisioner dan data yang diperoleh akan diuji secara univariat dan bivariat menggunakan uji Chi Square. Hasil penelitian menunjukan bahwa ibu hamil yang berusia 21-35 tahun sebanyak 25 orang (73,5%), dengan pekerjaan sebagai ibu rumah tangga sebanyak 25 orang (73,5%), dan kehamilan anak pertama sebanyak 18 orang (47,4%), dengan persiapan persalinan yang baik sebanyak 29 orang (85,3%) serta tingkat kecemasan yang sangat berat sebanyak 21 orang (61,8%). Berdasarkan hasil perhitungan Chi Square didapatkan P-value 0.000 < 0,05 yang artinya H0 ditolak dan Hα diterima. Terdapat hubungan antara persiapan persalinan ibu hamil trimester III dengan tingkat kecemasan saat pandemi covid-19. Diharapkan bagi tenaga kesehatan bisa mempertahankan konseling secara teratur kepada ibu hamil tentang persiapan persalinan dan tentang kecemasan pada ibu hamil saat melakukan pemeriksaan.Kata Kunci : Covid-19, Kecemasan, Persiapan Persalinan